2019
DOI: 10.1071/cp19027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a long-established silvopastoral Brachiaria decumbens system: plant characteristics and feeding value for cattle

Abstract: One of the main challenges of using a silvopastoral system (SPS) is maintaining pasture and animal productivity over time. Our objective was to compare the productive characteristics and nutritive value of signal grass (Brachiaria decumbens cv. Basilisk) and the liveweight gain of dairy heifers in a SPS and open pasture (OP, signal grass under full sunlight) during the rainy seasons of four experiments between 2003 and 2016, which characterised systems from their 6th to 19th years after establishment in south-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
12
1
1
Order By: Relevance
“…Several studies have shown that at moderate levels of shading (20%-29%), it is possible to sustain Brachiaria spp. pasture productivity (do Nascimento et al, 2019;Lima, Paciullo, Silva, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that at moderate levels of shading (20%-29%), it is possible to sustain Brachiaria spp. pasture productivity (do Nascimento et al, 2019;Lima, Paciullo, Silva, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…grandis trees had an average height of 29 m and DBH of 45 cm, with 50 trees per hectare. The A. mangium trees were 14.2 m tall and 32 cm DBH, with 16 trees per hectare after 19 years of growth (Lima, Paciullo, Silva, et al, 2019).…”
Section: Tree Measurements and Shading Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…Among the practices proposed by the Brazilian Low Carbon Agriculture Plan (Brazil 2021), integrated crop-livestock-forest (ICLF) systems (also known as agrosilvopastoral systems) stand out as a sustainable alternative to overcome grassland degradation, while keeping livestock profitable (Carnevalli et al 2019;Lima et al, 2019;Resende et al 2020;Lemes et al 2021;Pezzopane et al 2021;Vieira Júnior et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical pastures such as Brachiarias and Panicums can adapt to a certain level of light restriction, although growth limitations may occur when shade levels are greater than 35 to 40% Lima et al, 2019). PAR transmission around 60% represented reductions in the forage accumulation (Pontes et al, 2016;Pezzopane et al 2020a).…”
Section: Pasture Biomassmentioning
confidence: 99%